1998
DOI: 10.1086/301959
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of A3243G, the Mutation for Mitochondrial Encephalomyopathy, Lactic Acidosis, and Strokelike Episodes: Prevalence of the Mutation in an Adult Population

Abstract: Mitochondrial diseases are characterized by considerable clinical variability and are most often caused by mutations in mtDNA. Because of the phenotypic variability, epidemiological studies of the frequency of these disorders have been difficult to perform. We studied the prevalence of the mtDNA mutation at nucleotide 3243 in an adult population of 245,201 individuals. This mutation is the most common molecular etiology of MELAS syndrome (mitochondrial encephalomyopathy, lactic acidosis, and strokelike episode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
238
7
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(257 citation statements)
references
References 29 publications
7
238
7
5
Order By: Relevance
“…These current results for mtDNA mutations are similar to that reported previously in adult patients with mitochondrial disease in the North East of England a decade earlier and as such act as comparative data 3. Although the frequency of mtDNA mutations remain stable in our patient cohort, the point prevalence for the m.3243A>G mutation remains significantly lower than the frequency reported by Majamaa et al21 The reasons for this remain unclear. However, given that the point prevalence figures remain stable in the intervening decade in this English cohort, the genetic background and population structure may play a more significant role than study design in creating variability in prevalence rates than originally purported 3.…”
Section: Discussionsupporting
confidence: 91%
“…These current results for mtDNA mutations are similar to that reported previously in adult patients with mitochondrial disease in the North East of England a decade earlier and as such act as comparative data 3. Although the frequency of mtDNA mutations remain stable in our patient cohort, the point prevalence for the m.3243A>G mutation remains significantly lower than the frequency reported by Majamaa et al21 The reasons for this remain unclear. However, given that the point prevalence figures remain stable in the intervening decade in this English cohort, the genetic background and population structure may play a more significant role than study design in creating variability in prevalence rates than originally purported 3.…”
Section: Discussionsupporting
confidence: 91%
“…A population-based study of the m.3243A4G mutation revealed the mutation in 7.4% of patients with maternally inherited HL in northern Finland. 38 In this study, this mutation was demonstrated to have a prevalence of 2.4% in the cases of Japanese hereditary HL, and this frequency is very close to that previously reported in Japan. 39 This screening system detected the m.8348A4G mutation in the MT-TK gene in a 6-year-old boy (patient TMD 408) with SNHL ( Figure 2a).…”
Section: Discussionsupporting
confidence: 88%
“…4c). Only wild-type signals were seen in the sample we investigated, which is expected considering the low frequency of the mutation in the general population 24 .…”
Section: In Situ Genotyping Of Mitochondrial Genomesmentioning
confidence: 64%